Societal Change, Care Need and Long-Term Care Workforce in Selected European Countries - Erika Schulz; Johannes Geyer (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper aims to show the impact of societal change on the demand and supply of long-term care workforce. As age is the major driver of the need for care the growth in the number of elderly and oldest old will increase the demand for long-term care workforce. Caregiving to the elderly is predominantly the task of the family in almost all European countries. However, the majority of European countries provide some kind of formal care either in institutions, at home or as cash benefits. The amount of provided publicly financed long-term care services and the required formal workforce spread widely across the European countries depending on the long-term care system and the financial resources. We selected five countries: Denmark, Germany, Italy, Poland and Slovakia which represent different long-term care systems and financial resources. In all studied countries the demand for long-term care workforce will increase significantly. Although also the informal care giving potential aged 50+ is expected to increase, the increase in the demand for formal care workforce is projected to be higher than the supply. The current shortage of nursing and caring personnel will be strengthened. This requires an expansion of recruitment and retention strategies.
Additional information: This publication was produced as part of the NEUJOBS project, funded by the European Commission through the 7th Framework Programme under contract no. 266833 (http://www.neujobs).; info:eu-repo/grantAgreement/EC/FP7/266833
Keywords: 330; Gesundheitsberufe; Pflegeberufe; Gesundheitswesen; Deutschland; Slowakei; Dänemark; Italien; Polen